JURIDICAL ANALYSIS OF CHEMICAL CASTRATION CRIME IN HUMAN RIGHTS PERSPECTIVE AND KODEKI - Novie Carmelita (Fakultas Hukum Universitas Dwijendra, 2021)
ABSTRACT The Government in Law of Republic Indonesia Number 17 of 2016 concerning Determination of Substitute Government Regulations in Law of Republic Indonesia Number 1 of 2016 concerning the second amendment of Law Number 23 of 2002 Regarding Child Protection where there are sanctions for chemical castration against perpetrators considered violating to the article 33 paragraph 1 of Law Number 39 of 1999 Regarding Human Rights, and if a doctor is appointed as the executor, this could also violate the Indonesian Medical Code of Ethics (KODEKI) which is a guideline for Indonesian doctors who are members of the Ikatan Dokter Indonesia (IDI) or Indonesian Doctors Association in their medical practice. Legal conflicts occur between the aforementioned laws, so the type of research is normative using statutory approach. This research aims to examine and outline the main points of the legal basis for the regulation of chemical castration against paedophiles. The results showed that the government was completely unprepared in determining the stages of execution for convicted paedophiles. Determination has a double sanction, whereby the perpetrator becomes more brutal even though he is castrated. Psychological problems can be disturbed by the anti-androgen chemical injected into the body. Revenge takes on different forms. Keywords: Chemical Castration, Human Rights, Indonesian Medical Code of Ethics.